The News from Poems : Essays on the 21st-Century American Poetry of Engagement - Keniston, Ann, 1961-; Gray, Jeffrey, 1944- (Book collections on Project MUSE., 2016)
"The News from Poems examines a subgenre of recent American poetry that closely engages with contemporary political and social issues. This "engaged" poetry features a range of aesthetics and focuses on public topics from climate change, to the aftermath of recent wars in Afghanistan and Iraq, to the increasing corporatization of U.S. culture. The News from Poems brings together newly commissioned essays by eminent poets and scholars of poetry and serves as a companion volume to an earlier anthology of engaged poetry compiled by the editors. Essays by Bob Perelman, Steven Gould Axelrod, Tony Hoagland, Eleanor Wilner, and others reveal how recent poetry has redefined our ideas of politics, authorship, identity, and poetics. The volume showcases the diversity of contemporary American poetry, discussing mainstream and experimental poets, including some whose work has sparked significant controversy. These and other poets of our time, the volume suggests, are engaged not only with public events and topics but also with new ways of imagining subjectivity, otherness, and poetry itself"--